The learning self : understanding the potential for transformation - Tennant, Mark. (San Francisco : Jossey-Bass, 2012)
'This book examines the kind of learning that brings about significant personal change (transformational learning), and its overall theme is that individuals can be agents in their own formation by understanding and acting on the circumstances and forces that surround and shape them.Education beyond schooling has a long history of interest in the development and transformation of the self. A range of programs exist, from those which aim to promote. self-development as an end in itself, to those programs in which changes to the self are seen as being a necessary component of broader organizational or social change. There are also a host of programs where self-change is important in its own right, but where there is a broader social problem being addressed (e.g. programs for AIDS patients, those addicted to drugs, diabetes sufferers, recent migrants, soon-to-be-parents, etc.). In all these programs there are implicit or explicit theorizations concerning the nature of the self and the way the self relates to others or to society, which are a necessary part of our conception of the possibility of self-change and the associated practices deployed for the purpose of change.The book aims to: promote, among educators and others with an educational dimension to their work, a more critical approach to their learning designs and practices; equip individuals with a framework for understanding and being agents of their own self-formation and change. '--
Includes bibliographical references (pages 173-190) and index.
Keywords: Transformative learning; Learning, Psychology of; Adult learning